THEORETICAL AND HISTORICAL FOUNDATIONS OF QIRA’AT IN THE SCIENCE OF TAFSIR (The Journal of Interdisciplinary Human Studies, 2026)
This article investigates the theoretical and methodological underpinningsof Qira’at (Quranic recitations) within the broader framework of Tafsir (exegesis). Itanalyzes the historical trajectory of Quranic codification, beginning with the foundationalefforts of Caliph Uthman ibn Affan and progressing through the scholarly contributionsof Ibn Mujahid, Al-Shatibi, and Ibn al-Jazari. The study identifies five pivotal stages ofcanonization that transformed the oral tradition into a standardized academic discipline.Furthermore, it explores the integration of recitation variants in classical exegeticalworks, such as those by Al-Tabari, Al-Zamakhshari, and Al-Nasafi, highlighting howthese variants influence legal and linguistic interpretations in Islamic scholarship.
Keywords: Quranic recitations; Qira’at, Tafsir; Canonization; Uthmanic Mus’haf; Ibn Mujahid; Islamic Intellectual History